ANALYSIS OF LITERATURE PSYCHOLOGY IN THE SOEKRAM TRILOGY NOVEL BY SAPARDI DJOKO DAMONO - Aam Nurjaman; Sri Rahayu Dwi Astuti; Wildan F. Mubarock; Ruyatul Hilal Mukhtar; Vriski Aviandika (UNIVERSITAS PAKUAN, 2022)
This study aims to describe and determine the psychological value of literature in the novel Trilogi Soekram by Sapardi Djoko Damono. The method used for this research is a descriptive qualitative method. This method is used to describe systematically, factually and accurately about the psychological value of literature, especially the personality structure according to Sigmund Freud's id, ego, superego in the novel. The techniques used in this research are document study and content analysis. The type of study technique that this researcher uses is collecting quotes from the novel Trilogi Soekram. The data is in the form of quotations containing the psychological value of literature. The analysis technique is done through grouping and analyzing data. The psychological value of literature on the personality structure of the id with a total of 22 quotes, the personality structure of the ego with a total of 19 quotes, and the personality structure of the superego with a total of 13 quotes. The results of this study become one of the alternative teaching materials used in high schools (SMA) and universities. The values generated from this research can be used as teaching materials aimed at shaping the character through the personality values of students related to behavior in schools and colleges.